2005
DOI: 10.1080/10635150500354837
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetics of the Siphonophora (Cnidaria), with Implications for the Evolution of Functional Specialization

Abstract: Siphonophores are a group of pelagic colonial hydrozoans (Cnidaria) that have long been of general interest because of the division of labor between the polyps and medusae that make up these "superorganisms." These polyps and medusae are each homologous to free living animals but are generated by an incomplete asexual budding process that leaves them physiologically integrated. They are functionally specialized for different tasks and are precisely organized within each colony. The number of functional types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
163
3
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(182 citation statements)
references
References 43 publications
13
163
3
3
Order By: Relevance
“…We did not however find support for Codonophora (sensu Dunn et al, 2005). Our ML analysis placed the cystonect Physalia as the sister taxon to Calycophorae (Figure 1), not as the earliest diverging member of siphonophores (Collins 2002;Dunn et al, 2005). The MP analysis also recovered a probable paraphyletic Physonectae, but unlike the ML analyses, Physalia was nested within Calycophorae (Figure 2).…”
Section: Siphonophoraementioning
confidence: 73%
See 4 more Smart Citations
“…We did not however find support for Codonophora (sensu Dunn et al, 2005). Our ML analysis placed the cystonect Physalia as the sister taxon to Calycophorae (Figure 1), not as the earliest diverging member of siphonophores (Collins 2002;Dunn et al, 2005). The MP analysis also recovered a probable paraphyletic Physonectae, but unlike the ML analyses, Physalia was nested within Calycophorae (Figure 2).…”
Section: Siphonophoraementioning
confidence: 73%
“…Collins (2002) placed the cystonect Physalia as sister to the other included siphonophores and suggested that Physonectae may be paraphyletic with respect to the Calycophorae. A later study (Dunn et al, 2005), that considered additional taxa and two genes (18S and 16S) found that cystonects form a monophyletic group that is sister to the remaining siphonophores and the paraphyly of Physonectae was recovered with significant support. Dunn et al (2005) erected the name Codonophora to refer to the clade comprising taxa assigned to Physonectae and Calycophorae (i.e.…”
Section: Siphonophoraementioning
confidence: 99%
See 3 more Smart Citations